Language and Identity on Facebook: an Online Ethnographic Study of Nicknames, Self-presentation and Religious Identity among a Sub-religious Group in Algeria. - Saoudi, Fayçal (Journal of Human Sciences, 2018)
Early research on nicknames and self-presentation online focused on naming and identity in chatting rooms, gaming platforms and emails. However, recent studies have shifted their interest to naming and identity constructions in more user-generated networks known as Social Networking Sites. Great research has been conducted in the subject in the western world due to its novelty and deep social meaning especially on Facebook. Nicknames have been proved accordingly to be an essential identity marker in SNSs. Although having this great importance, the subject has not received a great attention in the Arab world. In Algeria, most studies focused on code-switching and language contact on Facebook and Twitter in the light of the diglossic situation of the country. The present study investigates naming and identity constructions on Facebook among a sub-religious group in Algeria known as Salafis. Applying the discourse-centered ethnographic research methods, 150 Male Facebook accounts in a friends’ network were analyzed and interviews with 30 participants were conducted. The study argues that the use of nicknames was dominant among Algerian Salafis to promote the religious affiliation identity rather than social one on Facebook. Two categories of nicknames emerged: ‘implicit nicknames with place of origin reference’ and ‘explicit with religious affiliation reference’. The characteristics of such identities are described and the implications of these ﬁndings are discussed.